2004
DOI: 10.1111/j.1365-313x.2004.02171.x
|View full text |Cite
|
Sign up to set email alerts
|

A dehydration‐induced NAC protein, RD26, is involved in a novel ABA‐dependent stress‐signaling pathway

Abstract: SummaryArabidopsis thaliana RD26 cDNA, isolated from dehydrated plants, encodes a NAC protein. Expression of the RD26 gene was induced not only by drought but also by abscisic acid (ABA) and high salinity. The RD26 protein is localized in the nucleus and its C terminal has transcriptional activity. Transgenic plants overexpressing RD26 were highly sensitive to ABA, while RD26-repressed plants were insensitive. The results of microarray analysis showed that ABA-and stress-inducible genes are upregulated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
614
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 842 publications
(641 citation statements)
references
References 79 publications
19
614
1
7
Order By: Relevance
“…NAM) [11], stress responses (eg. ATAF1, RD26 and OsNAC6) [18,47,66] and leaf senescence (eg. NAP) [29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NAM) [11], stress responses (eg. ATAF1, RD26 and OsNAC6) [18,47,66] and leaf senescence (eg. NAP) [29].…”
Section: Resultsmentioning
confidence: 99%
“…NAC proteins have been implicated to participate in a wide range of plant developmental processes, including shoot apical meristem development [10,23-26], floral morphogenesis [27], lateral root development [15,28], leaf senescence [29,30], stress inducible flowering induction [31,32], embryo development [11], cell cycle control [33-35], hormone signaling [15,18,33,36], grain nutrient remobilization [30,37] and shoot branching determination [38]. Particularly, numerous NAC domain proteins have also been implicated in plant abiotic stresses and defense responses such as drought, salinity, cold shock, mechanical wounding and viral infection [18,20,28,36,39-47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brassica napus, nine members of the NAC (BnNAC) were identified for their differential expression after feeding with flea beetle and treatment of cold temperature (Hegedus et al 2003). In Arabidopsis, Tran et al (2004) and Fujita et al (2004) reported that three NAC genes ANAC019, ANAC055 and ANAC072 were induced by drought, salinity, and/or low temperature, and the transgenic Arabidopsis plants overexpressing these genes showed improved stress tolerance compared to the wild type. Furthermore, Proteins of these genes can bind to the promoter sequences with CATGTG motif .…”
mentioning
confidence: 99%
“…For example, transcript accumulation was observed for RD26 in response to cold stress [44], but this was not found with ATAF1 (data not shown). Recently, OsNAC6, a rice ortholog of ATAF1, was reported to be a positive contributor to disease resistance and salinity tolerance [29,30].…”
Section: Functional Overlap Between Ataf1 and Other Stressregulatory mentioning
confidence: 92%